Obesity Index That Better Predict Metabolic Syndrome: Body Mass Index, Waist Circumference, Waist Hip Ratio, or Waist Height Ratio - Abdulbari Bener; Mohammad T. Yousafzai; Sarah Darwish; Abdulla O. A. A. Al-Hamaq; Eman A. Nasralla; Mohammad Abdul-Ghani (Journal of Obesity)
Aim. The aim was to compare body mass index (BMI), waist circumference (WC), waist hip ratio (WHR), and waist height ratio (WHtR) to identify the best predictor of metabolic syndrome (MetS) among Qatari adult population. Methods. A cross-sectional survey from April 2011 to December 2012. Data was collected from 1552 participants followed by blood sampling. MetS was defined according to Third Adult Treatment Panel (ATPIII) and International Diabetes Federation (IDF). Receiver operating characteristics (ROC) curve analysis was performed. Results. Among men, WC followed by WHR and WHtR yielded the highest area under the curve (AUC) (0.78; 95% CI 0.74–0.82 and 0.75; 95% CI 0.71–0.79, resp.). Among women, WC followed by WHtR yielded the highest AUC (0.81; 95% CI 0.78–0.85 & 0.79; 95% CI 0.76–0.83, resp.). Among men, WC at a cut-off 99.5 cm resulted in the highest Youden index with sensitivity 81.6% and 63.9% specificity. Among women, WC at a cut-off 91 cm resulted in the highest Youden index with the corresponding sensitivity and specificity of 86.5% and 64.7%, respectively. BMI had the lowest sensitivity and specificity in both genders. Conclusion. WC at cut-off 99.5 cm in men and 91 cm in women was the best predictor of MetS in Qatar.